Fantástico mundo das cores - Carvalho, Genilza Aparecida Gonçalves de; Alencar, Rosania Aparecida Souza; Reis, Ana Serafin dos; Silvério, Agda Rodrigues Rios; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf